Mini Review: Potential Applications of Non-host Resistance for Crop Improvement - Lee, Seonghee; Whitaker, Vance M.; Hutton, Samuel F. (Frontiers in Plant Science, 2016)
Plant breeding for disease resistance is crucial to sustain global crop production. For decades, plant breeders and researchers have extensively used host plant resistance genes (R-genes) to develop disease resistant cultivars. However, the general instability of R-genes in crop cultivars when challenged with diverse pathogen populations emphasizes the need for more stable means of resistance. Alternatively, nonhost resistance is recognized as the most durable, broad-spectrum form of resistance against the majority of potential pathogens in plants and has gained great attention as an alternative target for managing resistance. While transgenic approaches have been utilized to transfer nonhost resistance to host species, conventional breeding applications have been more elusive. Nevertheless, avenues for discovery and deployment of genetic loci for nonhost resistance via hybridization are increasingly abundant, particularly when transferring genes among closely related species. In this mini review, we discuss current and developing applications of nonhost resistance for crop improvement with a focus on the overlap between host and nonhost mechanisms and the potential impacts of new technology.